Retrieval of a metallic obstruction from the root canal of a premolar using Masserann technique - A R Vivekananda Pai; Shugufta Mir; Rachit Jain (Wolters Kluwer Medknow Publications, 2013)
A metallic obstruction in the root canal blocks canal cleaning and shaping procedures and requires either bypassing or retrieval. Many methods have been recommended to retrieve a metallic obstruction from the root canal. This article describes the retrieval of a metallic obstruction from the root canal of a premolar using Masserann technique to facilitate endodontic retreatment. Masserann technique is said to have limited application in posteriors. However, in this case, the obstruction was successfully retrieved by employing Masserann technique which consisted of using a trephan to cut the dentine and extractor tube to retrieve the obstruction. The retrieved obstruction was found to be a separated H-file. Endodontic retreatment was completed following the detection and negotiation of an extra canal in the same tooth.